DETERMINATION OF PROTEOLYTIC ACTIVITY OF GASTRIC AND PANCREATIC JUICE USING PROTEIN-FAT SUBSTRATES (Лучшие интеллектуальные исследования, 2025)
Annotation: The effect of hydrolysis products of fats of various concentrations on the proteolytic activity (PF) of pancreatic and gastric juice was studied using casein precipitation (casein+tributyrin, casein sunflower oil). Under the influence of sunflower oil hydrolysis products, the total proteolytic activity of pancreatic juice has clearly decreased, but under the influence of tributyrin hydrolysis products, this indicator has not changed. Hydrolysis products of sunflower oil and tributyrin oil do not affect the overall proteolytic activity in the stomach acidity fan. We have seen a decrease in the proteolytic activity of the pancreas, which is clearly manifested in the fact that the concentration of the above fats increases in the content of casein +facemailing. Increased concentration of fats did not affect the proteolytic activity of gastric juice.